PEMBUATAN PAKAN IKAN BERBAHAN BAKU LOKAL DI DESA WISATA TARO KABUPATEN GIANYAR - BALI: PRODUCTION OF FISH FEED FROM LOCAL RAW MATERIALS IN THE TOURIST VILLAGE OF TARO, GIANYAR REGENCY - BALI - Gede Agus Surya Pratama; Zaenal Abidin; Sudiarta, Ketut; Putri Suryani, Sang Ayu Made; Putri Lestari, Dewi; Sudiarta, Gede; Darmadi, Ni Made; Semara Edi, Dewa Gede; Sugiana, Gusti Ngurah; Diah Mahesa, Wastu Ayu; Idris Affandi, Rangga (Jurnal Pengabdian Masyarakat Pesisir, 2025)
Feed is one of the most determining factors in cultivation activities, with good and correct feed making techniques it is expected to create fish feed with a formulation that is in accordance with the growth of catfish. The purpose of this community service is to improve the knowledge, attitudes and skills of fish farmers. The method of implementing the activity is through practice, discussion and question and answer. The results of the community service activities went well and correctly, participants were able to understand the material presented by the resource person including feed formulation, material selection and fish feed printing. The tools and materials used in this activity are feed printing machines (vertical and extruder) and scales. While the materials used are 25% fish meal, 22% soybean meal, 40% bran, 10% tapioca, 2% vitamins, 1% minerals